La Belle Époque from Eastern Africa: an individual experience of the "globalizing" world, 1898–1918. Issue 4 (2nd October 2019) - Robinson, Morgan
ABSTRACT: This article seeks to expand our historical understanding of late-nineteenth-century "globalization" through the letters of a female Christian convert living in southeastern Tanganyika. By examining the correspondence between Agnes Sapuli and her educational sponsor in England, the historian can begin to reconstruct the individual, subjective experience of turn-of-the-century global connectedness. In so doing, we find that in the so-called periphery, people were simultaneously plugged in to the global trends of connection and acceleration, while also being keenly aware of the precariousness of those links. Moreover, on the individual level, late-nineteenth and early-twentieth-century "globalization" included the growth of far-flung, but deeply important, affective relationships – relationships that often proved just as durable as railway ties and steamship routes.